Lead acid battery management system for solar harvesting system - Shazril, Shaedi (2013)
The first solar energy was introduced in this decade and from that time, there are many new solar technology equipment was made in vehicle, lighting and other. Since then, various technologies have emerged to make solar based technology equipment with battery or other. However there are still limitations on the development process especially in terms of the battery management technology which includes battery technology. The phrase battery management means differently to different people, for us, battery management is how to manage all the battery voltage to be all same together and not so far difference when in used. Generally the energy battery management system of a solar equipment system includes the requirement to ensure that electrical power flow from the Photovoltaic to the loads will be monitored and optimised. Load behaviour significantly affects the solar equipment especially the battery. Hence, proper load battery management strategy is important to draw maximum power from the Photovoltaic module. A maximum power point tracker device must be used between the photovoltaic module and battery to boost the battery charging rate. Some back up batteries are needed in the system to eliminate unexpected system shutdown. As a result, an appropriate system that is focus on lead acid battery should be determined at the design stage to ensure for optimum battery management system can be built.